Imitation in children's locomotor play. (3rd August 2018) - Hoey, Elliott M.; DeLiema, David; Chen, Rachel S. Y.; Flood, Virginia J.
Abstract : Children commonly engage in social locomotor play—the horsing around, running about, and physical contact characteristic of playgrounds and neighborhood streets. To adults and outsiders, this activity may look like undisciplined chaos. However, the very recognizabilitly of locomotor play—the fact that children observably pull it off together as a discriminate activity—points to a set of shared practices for its accomplishment. In this article, we investigate children's methods and resources for organizing social locomotor play. Using video recordings of 5-6yo children playing during an immersive technologically-mediated science lesson, our analysis shows in fine detail some of the orderliness of social locomotor play. In particular, we demonstrate how children use imitation to organize the initiation and progression of this activity.